Optical and structural properties of V2O5 electrochromic thin films - Tan, Ming Yue; Chan, Kah Yoong; Thien, Gregory Soon How; Tan, Kar Ban; Murthy, H. C. Ananda; Au, Benedict Wen Chen (Multimedia University Press, 2024)
The increase in global temperature has led to a significant surge in energy consumption within the air conditioning industry, resulting in environmental deterioration. Electrochromic (EC) windows have emerged as a promising solution to address these challenges. Vanadium pentoxide (V2O5) stands out among all metal oxide materials due to its remarkable EC properties, including substantial Li+ ion insertion capacity and multicolor capabilities. Despite the potential of V2O5, there remains a lack of comprehensive research on the structural and optical properties of V2O5films with varying thicknesses. Therefore, this study aims to investigate the structural and optical propertiesof V2O5 thin films with thicknesses ranging from 68 to 612 nm. By employing the sol-gel spin coating method, V2O5 thin films were fabricated and analyzed using Xray diffraction (XRD) spectroscopy and ultravioletvisible (UV-Vis) spectrophotometry. The fabricated V2O5 thin films with thicknesses of 68-340 nm demonstrated an average film transparency of 83%. XRD analysis further revealed that the V2O5 thin films reached their peak crystallinity at a thickness of 630 nm. Moreover, CV analysis revealed that the V2O5 device, with a thickness of 340 nm, exhibited a cathodic peak current of -1.63 mA, indicating its excellent ability tofacilitate Li+ ion diffusion. Additionally, CA measurements displayed a high optical modulation of 37.78%. Ultimately, this research contributes to thedevelopment of energy-efficient solutions for sustainable environmental practices.